(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Abstract Cartoon movie are designed not only to entertain children, but cartoons can be also used to teach and educate the children. The objectives of the study that are to find out whether “Upin and Ipin” cartoon movie can improve the students’ vocabulary and to know whether there is an increase between pre test and post test about the types of vocabulary of "Upin and Ipin" cartoon movie. The method of the research used pre-experimental method with one group pre-test and post-test design. The pre-test administered in order to know students’ vocabulary achievement after. Conducted treatment by using upin and ipin cartoon movie episode 16 Spiritual Night. The subject of the study was seventh grade students of SMP Angkasa Mandai. There were 30 students. Based on finding and discussion, it can be seen that this research shows us that the using Upin and Ipin cartoon movie episode 16 Spritual Night can help students to improve understanding on vocabulary mastery about kinds of vocabulary. After two test was done, there is significant improvement of vocabulary by using Upin and Ipin cartoon movie episode 16 Spritual Night. Pre test mean score (49.67 %) and the post test mean score (88%). The role of media is very important to increasing achievement vocabulary mastery. Therefore, to help the students to remember vocabulary and practice in learning language. It is one of solution to be used as appropriate method in teaching learning process